Мобилизация природно-рекреационных ресурсов Грузии в условиях распространения COVID-19: организационно-экономический аспект - Паресишвили, О.; Кварацхелиа, Л.; Гамезардашвили, Д.; Мирзаева, В. (Економіка природокористування і сталий розвиток, 2020)
На примере Грузии проанализированы вопросы эффективного использования природно-рекреационных ресурсов в контексте реагирования на глобальный вызов – пандемию COVID-19. Осуществлено сопоставление наиболее популярных курортов Грузии, исходя из их физико-географических характеристик, основных лечебных факторов, медицинских показаний и предлагаемых методов лечения. Подчеркнуто целесообразность активного использования другими странами имеющегося природно-рекреационного потенциала в реабилитационных целях, налаживание обмена опытом в этой сфере. The article, through the example of Georgia, examines the problem of efficient using natural-recreational resources in the context of responding to the global challenge of 2020 – COVID-19 pandemic. In difficult conditions, methods are being developed to solve the problems associated with the disease. After acute phase of the disease, patients have to undergo a long-term rehabilitation in order to recover functioning impaired organs and systems of organism. Health-improving practices based on natural-recreational factors would hasten and improve recovery process. Georgia has high potential for the development of the mentioned sphere. For a long time, natural factors of Georgia have been used for therapy, preventive care and rehabilitation of people; there are many world-famous health-resorts in Georgia. The authors propose to use available medical-rehabilitation potential for those who had COVID-19. Positive effect on patients may be made by health-improving measures used in Georgian resorts such as active and passive climatotherapy, air and sun baths, spa treatment, mineral water drinking, bathes, inhalations, mudtherapy, etc.
The article analyzes Georgian resorts based on the main medical factors as well as in regional context. Based on the nature of resort resources, regional features and other factors, the territory of Georgia has been divided into 12 resort and recreational areas, differing in their specialization and structure of medical institutions. A summary table contains brief physical-and-geographical characteristics and medical factors of the most popular Georgian resorts along with provided methods of treatment and therapeutic indications. It is emphasized that there is no need to completely reorient existing healthcare facilities, they will be function in the ordinary course, and to serve post-COVID-19 patients special programs will be drawn up. Taking into consideration a great number of COVID-19-patients throughout the world and numerous disease-induced complications, the article proposes to intensify using available natural-recreational potential for rehabilitation purpose and to establish international contacts and experience exchange in this sphere. Досліджено проблему ефективного використання природно-рекреаційних ресурсів Грузії в контексті реагування на глобальний виклик 2020 року – пандемію COVID-19. З’ясовано, що після закінчення гострої фази хвороби пацієнти змушені проходити досить тривалий реабілітаційний курс для відновлення функціонування пошкоджених органів і систем організму. Доведено можливість прискорення й оптимізації процесу відновлення за допомогою оздоровчих процедур із застосуванням природних чинників. Наголошено, що Грузія має великий потенціал розвитку зазначеного напряму, природні фактори країни здавна використовувалися для лікування, профілактики і реабілітації людей, багато курортів заслужено користуються світовою популярністю. Рекомендовано застосування лікувально-оздоровчого потенціалу і для громадян, які перехворіли на COVID-19, оскільки заходи, що практикуються на курортах, зокрема активна і пасивна кліматотерапія, повітряні й сонячні ванни, термальні та мінеральні води, грязелікування тощо, обумовлюють позитивний ефект щодо стану здоров’я пацієнтів.
Проаналізовано курорти Грузії, виходячи з основних лікувальних факторів, а також у регіональному розрізі. Залежно від характеру курортних ресурсів, місцевих особливостей та інших факторів територію країни поділено на 12 курортно-рекреаційних зон, що відрізняються своєю спеціалізацією та структурою лікувальних закладів. Наведено короткі фізико-географічні характеристики, лікувальні фактори найбільш популярних курортів, пропоновані методи лікування і медичні показання. Наголошено на недоцільності повної переорієнтації лікувально-оздоровчих установ, тобто їх функціонуванні у звичайному режимі та розробленні відповідних програм для обслуговування постраждалих від COVID-19. Зважаючи на велику кількість хворих у світі і численні ускладнення після перенесеної хвороби, рекомендовано більш активне використання природно-рекреаційного потенціалу країни в реабілітаційних цілях, налагодження міждержавного обміну досвідом у цій сфері.